Energy-Efficiency for IoT System With Cache-Enabled Fixed-Wing UAV Relay - Kang Song; Jifa Zhang; Zhengxia Ji; Jing Jiang; Chunguo Li (IEEE Access)
This paper studies the energy efficiency (EE) maximization problem of fixed-wing Unmanned aerial vehicles (UAVs) enabled Internet of Things (IoT) system, where an UAV is employed as an aerial relay with enough cache capacity to amplify and forward (AF) received signals between narrow band (NB)-IoT device and eNodeB. This paper optimizes the unconstrained trajectory of the UAV to maximize the EE of UAV-enabled IoT system to achieve the green communication. Due to the objective function is a fraction and is non-convex, it’s hard to solve the optimization problem. Therefore, this paper alternately optimizes trajectory in source subspace and destination subspace with the other fixed and comes up with an algorithm based on successive convex approximation (SCA) method and Dinkelbach method to obtain a local optimal solution. Numerical results show that the proposed UAV trajectory design method can obtain much bigger EE than the running track (RT) trajectory and circular trajectory. Besides, the proposed cache-enabled AF strategy can obtain much bigger EE than non cache-enabled AF strategy.